Neonatal septic arthritis: Clinical profile and predictors of outcome - Devi, R Usha; Bharathi, S Mangala; Anitha, M (Indian Journal of Child Health, 2016)
Background: Neonatal septic arthritis deserves a special attention due to its subtle signs and symptoms and catastrophic consequences. There is paucity of literature regarding the clinical profile and predictors of outcome in neonatal septic arthritis. Objectives: The objective was to study the clinical profile of neonates admitted with septic arthritis, their clinical and radiological outcomes on follow-up, and factors that predict outcomes. Methodology: Neonates with septic arthritis as assessed by retrospective case sheet review were included. Prospective data collection of clinical and radiological outcomes was done during follow-upvisits. Children with good outcomes (controls) were compared to those with poor outcomes (cases) subsequently to identify the predictors of outcomes using a nested case–control design. Results: Data of 70 neonates admitted with septic arthritis were collected. Single joint involvement was common (75.8%), and hip joint was the most common joint involved. Gram-negative organisms were predominant (72%), and Klebsiella was the most common organism isolated from joint aspirate (36%), followed by Escherichia coli and Staphylococcus aureus. Of 52 babies who turned for follow-up, half had poor outcomes. In univariate analysis,multiple joint involvement (odds ratio [OR] 4.79, [confidence interval (CI): 1.14-20.21]), pre-intervention period ?7 days (OR 92, [CI: 14.06-601.9]), culture positive joint aspirate (OR 3.70, [CI: 1.55-11.86]), and restricted range of joint movements at discharge (OR 83.3, [CI: 9.2-749.9]) were significantly associated with poor outcomes. Pre-intervention period ?7 days (adjusted OR 107.99, [CI: 5.16-2258.8]) and restricted joint mobility at discharge (adjusted OR 139.53, [CI: 9.03-2154.04]) were the independent predictors of poor overall outcome by logistic regression analysis. Conclusions: Long pre-intervention period and restricted joint mobility at discharge were independent predictors of poor outcome in neonatal septic arthritis. We emphasize the importance ofearly diagnosis, prompt referral to tertiary centers, timely surgical intervention, appropriate measures to ensure good joint mobility, and regular follow-up in these neonates to achieve best outcomes.